A ceramifiable silicone rubber material and a method for producing the same

By combining methyl vinyl silicone rubber with specific ceramic fillers, the problems of high preparation cost and insufficient performance of ceramicized silicone rubber have been solved. This has enabled molding at room temperature and ceramicization strength at 500°C, resulting in ceramicized silicone rubber with both excellent temperature resistance and low shrinkage.

CN119019180BActive Publication Date: 2026-11-06HARBIN INST OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411101096.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-12
Publication Date
2026-11-06
Estimated Expiration
2044-08-12

AI Technical Summary

Technical Problem

The existing preparation process of ceramicized silicone rubber materials requires specialized equipment and high-temperature molding, which is costly. Furthermore, the ceramicization effect is poor below 800°C, resulting in low flexural strength, high shrinkage, and insufficient temperature resistance.

Method used

A ceramicized silicone rubber with excellent temperature resistance and low shrinkage is formed by combining methyl vinyl silicone rubber with specific ceramic fillers, including alumina, low melting point glass powder, and aluminum dihydrogen phosphate, through room temperature molding and eutectic reaction at 500°C.

Benefits of technology

It achieves molding at room temperature and vitrification strength at 500℃. The ceramicized silicone rubber formed during the ceramicization process has low shrinkage, high flexural strength and temperature resistance, making it suitable for high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119019180B_ABST
    Figure CN119019180B_ABST
Patent Text Reader

Abstract

This invention provides a ceramicized silicone rubber material composed of methyl vinyl silicone rubber and a ceramic-forming filler. The ceramic-forming filler comprises a filler matrix, a co-solvent, a binder, a heat-compensating agent, a shrinkage inhibitor, and a flame retardant. After mixing the methyl vinyl silicone rubber and the ceramic-forming filler, it can be molded at room temperature without specialized equipment or secondary vulcanization. Furthermore, the ceramic-forming filler, composed of the filler matrix, co-solvent, binder, heat-compensating agent, shrinkage inhibitor, and flame retardant, exhibits good ceramicization strength at 500°C. During the ceramicization process, the methyl vinyl silicone rubber undergoes thermal decomposition. Through optimal selection of the components in the ceramic-forming filler, the thermally decomposed methyl vinyl silicone rubber undergoes a eutectic reaction with the components in the ceramic-forming filler, resulting in a ceramicized silicone rubber that possesses both excellent temperature resistance and mechanical properties, as well as a low shrinkage rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of silicone rubber technology, and in particular to a ceramicized silicone rubber material and its preparation method. Background Technology

[0002] Ceramicized silicone rubber materials behave similarly to ordinary rubber materials at room temperature, exhibiting characteristics such as non-toxicity, high-temperature resistance, excellent electrical insulation properties, and good processability. However, under high-temperature conditions, the material transforms from a flexible rubber into a hard ceramic body, ensuring internal safety. Particularly in aerospace, sealing, power transmission, construction, and electronics industries, fire-resistant and flame-retardant ceramicized silicone rubber with a certain strength has become a new area of ​​demand.

[0003] However, while the research on ceramicized silicone rubber is becoming increasingly diversified and multi-layered, it still faces many challenges. On the one hand, in the preparation process of ceramicized silicone rubber composites, in order to achieve the ceramicization function of silicone rubber, silicone rubber is usually mixed with a large amount of ceramic filler in an open mill or internal mixer, and then vulcanized at high temperature using specialized equipment. However, this method requires specialized equipment and high temperature molding, resulting in excessively high production and manufacturing costs. On the other hand, existing ceramicized silicone rubbers typically require a eutectic reaction at temperatures above 800°C to obtain high strength. Below 800°C, the ceramicization effect is poor, with a flexural strength of only about 2-3 MPa. In addition, due to the addition of a large amount of co-solvent, although the ceramicization transition temperature is lowered, the shrinkage rate of silicone rubber during the ceramicization process is high, and the temperature resistance is poor.

[0004] Therefore, based on the above problems, there is an urgent need to provide a new ceramicized silicone rubber material and its preparation method. Summary of the Invention

[0005] This invention provides a ceramicized silicone rubber material and its preparation method. The ceramicized silicone rubber can be molded at room temperature and has ceramicized strength at 500°C. Furthermore, the ceramicized silicone rubber formed after ceramicization has a low shrinkage rate, high flexural strength, and high temperature resistance.

[0006] In a first aspect, the present invention provides a ceramicized silicone rubber material, which is composed of silicone rubber and ceramic-forming filler; wherein the ceramic-forming filler is composed of a filler body, a co-solvent, a binding aid, a heat compensation agent, a shrinkage inhibitor, and a flame retardant.

[0007] Preferably, the methyl vinyl silicone rubber contains a platinum catalyst, and the content of the platinum catalyst is 0.5-1.0% of the total amount of methyl vinyl silicone rubber;

[0008] The viscosity of the methyl vinyl silicone rubber is 5000-20000 mPa·s, and the mass ratio of the methyl vinyl silicone rubber to the ceramic filler is 100:(100-200).

[0009] Preferably, the filler body is alumina, and the flux is low-melting-point glass powder.

[0010] Preferably, the adhesive is at least one of aluminum dihydrogen phosphate, aluminum polyphosphate, or aluminum metaphosphate.

[0011] Preferably, the thermal compensator is composed of silicon powder and aluminum powder; wherein the mass ratio of silicon powder to aluminum powder is (5-20):(5-20).

[0012] Preferably, the shrinkage inhibitor is alumina fiber cotton; wherein the fiber diameter of the alumina fiber cotton is 3-4 micrometers.

[0013] Preferably, the flame retardant is aluminum hydroxide.

[0014] Preferably, the ceramic filler is composed of the following components by weight: 40-80 parts of filler body, 10-20 parts of co-solvent, 0.5-5 parts of binder, 10-40 parts of heat compensator, 0.5-5 parts of shrinkage inhibitor and 5-13 parts of flame retardant.

[0015] More preferably, the ceramic filler is composed of the following components: 55-65 parts of filler body, 15-18 parts of co-solvent, 2-3 parts of binder, 15-25 parts of heat compensator, 2-3 parts of shrinkage inhibitor and 12-13 parts of flame retardant.

[0016] Secondly, the present invention provides a method for preparing the ceramicized silicone rubber material according to any one of the first aspects above, the method comprising the following steps:

[0017] (1) Mix methyl vinyl silicone rubber with ceramic filler to obtain a mixture;

[0018] (2) The mixture is placed in a mold for vulcanization to obtain flexible silicone rubber;

[0019] (3) The flexible silicone rubber is placed in a muffle furnace for heating and ceramicizing to obtain the ceramicized silicone rubber.

[0020] Preferably, in step (2), the temperature of the sulfidation reaction is 22-24°C and the time is 7-10 days.

[0021] Preferably, the vulcanization reaction is carried out at a temperature of 40-42°C for 5-6 hours.

[0022] Preferably, in step (3), the temperature for heating and vitrification is 500-1600℃, the heating rate is 10-30℃ / min, and the time is 30-90min.

[0023] Compared with the prior art, the present invention has at least the following beneficial effects:

[0024] The ceramicized silicone rubber material of this invention is composed of methyl vinyl silicone rubber and ceramic filler. After mixing, the methyl vinyl silicone rubber and ceramic filler can be molded at room temperature without the need for specialized equipment and secondary vulcanization. Furthermore, the ceramic filler, which consists of a filler body, a co-solvent, a binder, a heat compensator, a shrinkage inhibitor, and a flame retardant, has good ceramicization strength at 500°C. During the ceramicization process, the methyl vinyl silicone rubber undergoes thermal decomposition. Through the optimization of each component in the ceramic filler, the thermally decomposed methyl vinyl silicone rubber undergoes a eutectic reaction with the components in the ceramic filler, thereby resulting in a ceramicized silicone rubber that possesses both excellent temperature resistance and mechanical properties, as well as a low shrinkage rate. Attached Figure Description

[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0026] Figure 1 This is an XRD pattern of a ceramicized silicone rubber material provided in Embodiment 1 of the present invention at different temperatures; wherein, the horizontal axis is the incident angle of the X-rays and the vertical axis is the diffraction intensity;

[0027] Figure 2 This is a macroscopic appearance change diagram of a ceramicized silicone rubber material provided in Embodiment 1 of the present invention after being ceramicized at 1600℃ for different times;

[0028] Figure 3 This is a macroscopic appearance change diagram of a ceramicized silicone rubber material provided in Embodiment 1 of the present invention after ceramicization at different temperatures; in the diagram, the temperatures from top to bottom are 500℃, 600℃, 800℃, 1000℃, 1200℃, 1400℃ and 1600℃ respectively.

[0029] Figure 4 This is a macroscopic appearance change diagram of a ceramicized silicone rubber material after ceramicization at different temperatures, provided in Embodiment 2 of the present invention.

[0030] Figure 5 This is a macroscopic appearance change diagram of a ceramicized silicone rubber material after ceramicization at different temperatures, provided in Embodiment 3 of the present invention.

[0031] Figure 6 This is a macroscopic appearance change diagram of a ceramicized silicone rubber material after ceramicization at different temperatures, provided in Embodiment 4 of the present invention.

[0032] Figure 7 This is a macroscopic appearance change diagram of a ceramicized silicone rubber material after ceramicization at different temperatures, provided in Embodiment 5 of the present invention.

[0033] Figure 8 This is a macroscopic appearance change diagram of a ceramicized silicone rubber material provided in Embodiment 6 of the present invention after being ceramicized at different heating rates to 1600℃;

[0034] Figure 9 This is a macroscopic appearance change diagram of a ceramicized silicone rubber material before and after ceramicization, provided in Comparative Example 4 of this invention. Detailed Implementation

[0035] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0036] This invention provides a ceramicized silicone rubber material, which is composed of methyl vinyl silicone rubber and ceramic-forming filler; wherein the ceramic-forming filler is composed of a filler body, a co-solvent, a binding aid, a heat compensation agent, a shrinkage inhibitor, and a flame retardant.

[0037] The ceramicized silicone rubber material in this embodiment of the invention is composed of methyl vinyl silicone rubber and ceramic filler. After mixing, the methyl vinyl silicone rubber and ceramic filler can be molded at room temperature without the need for specialized equipment and secondary vulcanization. Furthermore, the ceramic filler, which is composed of filler body, co-solvent, binder, heat compensation agent, shrinkage inhibitor and flame retardant, has good ceramicization strength at 500°C. During the ceramicization process, the methyl vinyl silicone rubber undergoes thermal decomposition. By optimizing the components in the ceramic filler, the thermally decomposed methyl vinyl silicone rubber undergoes a eutectic reaction with the components in the ceramic filler, thereby making the formed ceramicized silicone rubber have both excellent temperature resistance and mechanical properties, as well as a low shrinkage rate.

[0038] According to some preferred embodiments, the methyl vinyl silicone rubber contains a platinum catalyst, the content of which is 0.5-1.0% of the total amount of methyl vinyl silicone rubber (e.g., 0.5%, 0.8%, 0.9%, or 1.0%); the viscosity of the methyl vinyl silicone rubber is 5000-20000 mPa·s (e.g., 5000 mPa·s, 8000 mPa·s, 10000 mPa·s, 15000 mPa·s, or 20000 mPa·s); and the mass ratio of the methyl vinyl silicone rubber to the ceramic filler is 100:(100-200) (e.g., 100:100, 100:150, or 100:200).

[0039] In this embodiment of the invention, a certain viscosity of methyl vinyl silicone rubber is selected, and a certain amount of ceramic-forming filler is added. The two can be vulcanized and molded at room temperature. The molding process is simple and does not require professional equipment or secondary vulcanization reaction. Furthermore, by controlling the mass ratio of methyl vinyl silicone rubber to ceramic-forming filler, it is beneficial to prepare ceramicized silicone rubber materials with excellent high-temperature resistance, mechanical properties, and low thermal shrinkage. Experiments of this invention have confirmed that as the amount of ceramic-forming filler added increases, it is beneficial to ensure a low mass loss rate and a low shrinkage rate of the ceramicized silicone rubber material, while also enhancing the mechanical strength of the ceramicized silicone rubber material. However, the amount of ceramic-forming filler added should not be too much. Too much ceramic-forming filler will result in excessive viscosity, which can easily cause the ceramic-forming filler to agglomerate, making it impossible to ensure the uniformity of the ceramic-forming filler mixture, thereby affecting the ceramicization performance. At the same time, the high viscosity also greatly reduces the processing performance.

[0040] According to some preferred embodiments, the filler body is alumina, the co-solvent is low-melting-point glass powder, and the binder is at least one of aluminum dihydrogen phosphate, aluminum polyphosphate, or aluminum metaphosphate.

[0041] In this embodiment of the invention, alumina is used as the main filler for ceramic-forming filler. On the one hand, alumina is a good reinforcing filler for silicone rubber; on the other hand, alumina has good temperature resistance, a stable crystalline phase at high temperatures, and can react with other components in the ceramic-forming filler, thereby further ensuring that the ceramicized silicone rubber material has excellent temperature resistance. Low-melting-point glass powder with a melting point of 350-580℃ is used as a flux. Low-melting-point glass powder can melt at temperatures below 600℃, which, while filling gaps, facilitates the eutectic reaction of the ceramic-forming filler, thereby improving the mechanical properties of the ceramicized silicone rubber. At the same time, aluminum dihydrogen phosphate, aluminum polyphosphate, and / or aluminum metaphosphate are used as binders. Before the eutectic reaction occurs, the above-mentioned raw materials can exert their binding properties, enhance the mechanical strength of the ceramicized silicone rubber material, and transform into Al(PO)4 at high temperatures, still playing a good binding role, thereby further enhancing the mechanical strength of the ceramicized silicone rubber in high-temperature environments.

[0042] According to some preferred embodiments, the thermal compensator is composed of silicon powder and aluminum powder; wherein the mass ratio of silicon powder to aluminum powder is (5-20):(5-20) (for example, it can be 5:5, 5:15, 5:20, 5:10, 10:5, 20:5, 15:5, 15:20 or 20:20).

[0043] In this embodiment of the invention, silicon powder and aluminum powder are used as heat compensation agents during the ceramization process. On the one hand, silicon powder and aluminum powder can undergo an oxidation reaction under certain temperature and oxygen-containing conditions to form silicon dioxide and alumina with certain temperature resistance, thereby achieving heat compensation, reducing the mass loss rate, and compensating for shrinkage. On the other hand, when a higher ceramicization temperature is reached, the products formed by the oxidation of silicon powder and aluminum powder can further react with other components to form a high-temperature resistant ceramic phase, thereby further enhancing the temperature resistance of the ceramized silicone rubber material. Simultaneously, by rationally controlling the mass ratio of silicon powder and aluminum powder in the heat compensation agent, it is beneficial to further enhance the dimensional stability of the ceramized silicone rubber material.

[0044] According to some preferred embodiments, the shrinkage inhibitor is alumina fiber cotton; wherein the fiber diameter of the alumina fiber cotton is 3-4 micrometers (for example, it can be 3 micrometers, 3.5 micrometers or 4 micrometers); and the flame retardant is aluminum hydroxide.

[0045] In this embodiment of the invention, by adding alumina fiber cotton with a certain fiber diameter to the ceramic filler, the alumina fiber cotton can not only effectively inhibit the shrinkage of the ceramicized silicone rubber material during the ceramicization process of methyl vinyl silicone rubber and ceramic filler, but also has a certain temperature resistance. After reaching a certain temperature, the alumina fiber cotton can undergo a eutectic reaction with other components, thereby further enhancing the temperature resistance of the ceramicized silicone rubber material.

[0046] It should be noted that the alumina content in the alumina fiber cotton in the embodiments of the present invention is greater than 95%.

[0047] According to some preferred embodiments, the ceramic filler comprises the following components by weight: 40-80 parts of filler body (e.g., 40, 45, 50, 55, 60, 65, 70, 75, or 80 parts), 10-20 parts of co-solvent (e.g., 10, 15, or 20 parts), 0.5-5 parts of binder (e.g., 0.5, 1, 2, 3, 4, or 5 parts), 10-40 parts of heat compensator (e.g., 10, 20, 30, or 40 parts), 0.5-5 parts of shrinkage inhibitor (e.g., 0.5, 1, 2, 3, 4, or 5 parts), and 5-13 parts of flame retardant (e.g., 5, 8, 10, 12, or 13 parts).

[0048] In this embodiment of the invention, by rationally controlling the raw materials of each component in the ceramic filler, it is beneficial to enable methyl vinyl silicone rubber and the ceramic filler to undergo ceramicization, thereby forming a ceramicized silicone rubber material with excellent mechanical properties, temperature resistance, and low shrinkage. For example, if the amount of binder added is too low, it will not be conducive to ensuring good mechanical properties of the ceramicized silicone rubber material, but if the amount of binder added is too high, it will increase the thermal shrinkage of the ceramicized silicone rubber material. If the amount of shrinkage inhibitor added is too low, it will not be conducive to ensuring a low thermal shrinkage of the ceramicized silicone rubber material, but if the amount of shrinkage inhibitor added is too high, it will increase the viscosity of the system, reduce the mechanical strength of the ceramicized silicone rubber material, and cause the ceramicized silicone rubber material to warp at high temperatures. At the same time, a certain amount of heat compensator is beneficial to further enhance the temperature resistance of the ceramicized silicone rubber material, but too much heat compensator will increase the porosity of the material during the ceramicization process, thereby reducing the mechanical strength of the ceramicized silicone rubber material and increasing the thermal shrinkage.

[0049] According to some preferred embodiments, the ceramic filler is composed of the following components: 55-65 parts of filler body (e.g., 55, 58, 60, 62 or 65 parts), 15-18 parts of co-solvent (e.g., 15, 18 or 20 parts), 2-3 parts of binder (e.g., 2, 2.5 or 3 parts), 15-25 parts of heat compensator (e.g., 15, 18, 20 or 25 parts), 2-3 parts of shrinkage inhibitor (e.g., 2, 2.5 or 3 parts), and 12-13 parts of flame retardant (e.g., 12, 12.5 or 13 parts).

[0050] Since the content of each component in the ceramic filler has a significant impact on the performance of the ceramicized silicone rubber material, the embodiments of the present invention further optimize the content of each component in the ceramic filler, which is more conducive to preparing ceramicized silicone rubber materials with better comprehensive performance (such as thermal shrinkage rate, mechanical strength, high temperature resistance, etc.).

[0051] It should be noted that the cosolvent, filler body, binder, heat compensator and flame retardant in the embodiments of the present invention are all in powder form. At the same time, in order to ensure that the ceramic filler has good sintering performance and to prevent the ceramic filler from shrinking too much during the sintering process, the particle size of the above-mentioned powdered raw materials for the ceramic filler in the embodiments of the present invention is preferably 5-100 micrometers.

[0052] This invention also provides a method for preparing the ceramicized silicone rubber material described in any one of the above claims, the method comprising the following steps:

[0053] (1) Mix methyl vinyl silicone rubber with ceramic filler to obtain a mixture;

[0054] (2) The mixture is placed in a mold for vulcanization to obtain flexible silicone rubber;

[0055] (3) The flexible silicone rubber is placed in a muffle furnace for heating and ceramicizing to obtain the ceramicized silicone rubber.

[0056] In this embodiment of the invention, the ceramic fillers other than the heat shrink agent in the ceramic filler need to be stirred and mixed at a high mechanical speed (e.g., 800-1000 r / min), and then the speed is reduced (e.g., 300-500 r / min), and the heat shrink agent is added and mixed. This not only helps to ensure the uniformity between the components, but also avoids the heat shrink agent from being destroyed, thereby allowing it to better exert its heat shrinkage inhibition effect.

[0057] It should be noted that, in this embodiment of the invention, after the mixture is prepared, it is placed in a mold, vacuum degassed and extruded, so as to avoid air bubbles being trapped in the vulcanized silicone rubber.

[0058] According to some preferred embodiments, in step (2), the temperature of the vulcanization reaction is 22-24°C (e.g., 22°C, 23°C or 24°C), and the time is 7-10 days (e.g., 7 days, 8 days, 9 days or 10 days); or, the temperature of the vulcanization reaction is 40-42°C (e.g., 40°C, 41°C or 42°C), and the time is 5-6 hours (e.g., 5 hours, 5.5 hours or 6 hours).

[0059] In this embodiment of the invention, by using the above-mentioned types of silicone rubber and catalysts, the molding temperature of the silicone rubber material can be reduced, and it can be molded at room temperature. It is understood that as the temperature increases, it is beneficial to accelerate the molding of the silicone rubber material.

[0060] In some preferred embodiments, in step (3), the heating temperature for ceramicizing is 500-1600℃ (e.g., 500℃, 600℃, 800℃, 1000℃, 1200℃, 1400℃ or 1600℃), the heating rate is 10-30℃ / min (e.g., 10℃ / min, 15℃ / min, 20℃ / min, 25℃ / min or 30℃ / min), and the time is 30-90min (e.g., 30min, 40min, 50min, 60min, 70min, 80min or 90min).

[0061] In this embodiment of the invention, by controlling the types and contents of various components in the methyl vinyl silicone rubber and the ceramic filler, it is beneficial for the silicone rubber to have ceramic strength at a lower temperature (e.g., 500°C). For example, when the flexible silicone rubber is heated from room temperature to 1600°C at a heating rate of 10°C / min, the silicone rubber undergoes thermal decomposition at 400°C to 500°C during the temperature rise. At this temperature, the low-melting-point glass powder melts, which can inhibit its decomposition to a certain extent. At the same time, the shrinkage inhibitor and the bonding agent can play a role, thereby preventing the shrinkage rate of the ceramicized silicone rubber material from being too large and ensuring the good mechanical properties of the ceramicized silicone rubber material. When the temperature reaches 800-1000°C, the heat compensation agent is oxidized to achieve weight gain, and the bonding agent undergoes a crystal transformation, thereby better bonding other components together and ensuring the excellent mechanical properties of the ceramicized silicone rubber material. When the temperature reaches above 1000°C, the products formed by the components in the ceramic filler can undergo a eutectic reaction, thereby forming a mullite phase with higher heat resistance, which significantly enhances the temperature resistance and mechanical properties of the ceramicized silicone rubber material.

[0062] In summary, the present invention uses the above-mentioned types of silicone rubber and ceramic fillers to prepare ceramicized silicone rubber. The preparation process is simple, which not only allows the silicone rubber to be molded at room temperature without the need for special equipment and secondary vulcanization, but also enables the ceramicized silicone rubber material to be rapidly ceramicized at temperatures below 600°C. While having a low shrinkage rate (below 12%) and good ceramicization strength, it can withstand high temperatures up to 1600°C.

[0063] To more clearly illustrate the technical solution and advantages of the present invention, the following detailed description of a ceramicized silicone rubber material and its preparation method is provided through several embodiments.

[0064] In the following examples, the mass of methyl vinyl silicone rubber, catalyst, filler matrix, cosolvent, adhesive additive, heat compensator, shrinkage inhibitor and flame retardant are expressed in parts by weight.

[0065] Example 1:

[0066] (1) Stir 60 parts of filler body (alumina), 15 parts of flux (low melting point glass powder), 2.5 parts of binder (aluminum dihydrogen phosphate), 20 parts of heat compensation agent (silicon powder and aluminum powder in a 10:10 ratio) and 12.5 parts of flame retardant (aluminum hydroxide) at 1000 r / min for 30 min, then adjust the speed to 500 r / min, add 2.5 parts of shrinkage inhibitor (alumina fiber cotton) and stir for 30 min to obtain ceramic filler; mix 100 parts of methyl vinyl silicone rubber (platinum catalyst content is 0.5% of the total methyl vinyl silicone rubber) with 150 parts of ceramic filler manually or mechanically to obtain a mixture.

[0067] (2) The mixture is transferred into a mold, degassed under vacuum and extruded, and vulcanized at 23°C for 8 days to obtain flexible silicone rubber; the size is 100×80×3mm.

[0068] (3) Cut the vulcanized flexible silicone rubber into 80×10×3mm size, place it in a muffle furnace and heat it to 1600℃ at a heating rate of 10℃ / min and hold it for 30min-90min. After cooling to room temperature (22-25℃), take it out to obtain ceramicized silicone rubber material. The test results are shown in Table 1.

[0069] (4) Cut the vulcanized flexible silicone rubber into 80×10×3mm sizes, place it in a muffle furnace and heat it to 500℃, 600℃, 800℃, 1000℃, 1200℃, 1400℃ and 1600℃ respectively at a heating rate of 10℃ / min, and keep it at that temperature for 30min. After cooling to room temperature (22-25℃), take it out to obtain ceramicized silicone rubber material. The test results are shown in Table 2.

[0070] Example 2:

[0071] (1) Stir 40 parts of filler body (alumina), 15 parts of flux (low melting point glass powder), 2.5 parts of binder (aluminum dihydrogen phosphate), 20 parts of heat compensation agent (silicon powder and aluminum powder in a 10:10 ratio) and 7.5 parts of flame retardant (aluminum hydroxide) at 1000 r / min for 30 min, then adjust the speed to 500 r / min, add 2.5 parts of shrinkage inhibitor (alumina fiber cotton) and stir for 30 min to obtain ceramic filler; mix 100 parts of methyl vinyl silicone rubber (platinum catalyst content is 0.5% of the total methyl vinyl silicone rubber) with 150 parts of ceramic filler by manual or mechanical stirring to obtain a mixture.

[0072] (2) The mixture is transferred into a mold, degassed under vacuum and extruded, and vulcanized at 40°C for 6 hours to obtain flexible silicone rubber with a specification of 100×80×3mm.

[0073] (3) Cut the vulcanized flexible silicone rubber into 80×10×3mm size, place it in a muffle furnace and heat it to 600℃, 1000℃ and 1600℃ respectively at a heating rate of 10℃ / min and hold it for 30min respectively. After cooling to room temperature (22-25℃), take it out to obtain ceramicized silicone rubber material. The test results are shown in Table 3.

[0074] Example 3:

[0075] (1) Stir 60 parts of filler body (alumina), 15 parts of flux (low melting point glass powder), 0.5 parts of binder (aluminum polyphosphate), 20 parts of heat compensation agent (silicon powder and aluminum powder in a 10:10 ratio) and 7.5 parts of flame retardant (aluminum hydroxide) at 1000 r / min for 30 min, then adjust the speed to 500 r / min, add 2.5 parts of shrinkage inhibitor (alumina fiber cotton) and stir for 30 min to obtain ceramic filler; mix 100 parts of methyl vinyl silicone rubber (platinum catalyst content is 0.5% of the total methyl vinyl silicone rubber) with 150 parts of ceramic filler manually or mechanically to obtain a mixture.

[0076] (2) The mixture is transferred into a mold, degassed under vacuum and extruded, and vulcanized at 23°C for 10 days to obtain flexible silicone rubber with a specification of 100×80×3mm.

[0077] (3) Cut the vulcanized flexible silicone rubber into 80×10×3mm size, place it in a muffle furnace and heat it to 600℃, 1000℃ and 1600℃ respectively at a heating rate of 10℃ / min and hold it for 30min respectively. After cooling to room temperature (22-25℃), take it out to obtain ceramicized silicone rubber material. The test results are shown in Table 4.

[0078] Example 4:

[0079] (1) Stir 60 parts of filler body (alumina), 15 parts of flux (low melting point glass powder), 2.5 parts of binder (aluminum metaphosphate), 20 parts of heat compensation agent (silicon powder and aluminum powder in a 10:10 ratio) and 12.5 parts of flame retardant (aluminum hydroxide) at 1000 r / min for 30 min, then adjust the speed to 500 r / min, add 2.5 parts of shrinkage inhibitor (alumina fiber cotton) and stir for 30 min to obtain ceramic filler; mix 100 parts of methyl vinyl silicone rubber (platinum catalyst content is 0.5% of the total methyl vinyl silicone rubber) with 100 parts of ceramic filler manually or mechanically to obtain a mixture.

[0080] (2) The mixture is transferred into a mold, degassed under vacuum and extruded, and vulcanized at 23°C for 8 days to obtain flexible silicone rubber; the size is 100×80×3mm.

[0081] (3) Cut the vulcanized flexible silicone rubber into 80×10×3mm size, place it in a muffle furnace and heat it to 600℃, 1000℃ and 1600℃ respectively at a heating rate of 10℃ / min and hold it for 30min respectively. After cooling to room temperature (22-25℃), take it out to obtain ceramicized silicone rubber material. The test results are shown in Table 5.

[0082] Example 5:

[0083] (1) Stir 60 parts of filler body (alumina), 15 parts of flux (low melting point glass powder), 2.5 parts of binder (aluminum dihydrogen phosphate), 20 parts of heat compensation agent (silicon powder and aluminum powder in a 10:10 ratio) and 12.5 parts of flame retardant (aluminum hydroxide) at 1000 r / min for 30 min, then adjust the speed to 500 r / min, add 2.5 parts of shrinkage inhibitor (alumina fiber cotton) and stir for 30 min to obtain ceramic filler; mix 100 parts of methyl vinyl silicone rubber (platinum catalyst content is 0.5% of the total methyl vinyl silicone rubber) with 200 parts of ceramic filler manually or mechanically to obtain a mixture.

[0084] (2) The mixture is transferred into a mold, degassed under vacuum and extruded, and vulcanized at 23°C for 8 days to obtain flexible silicone rubber; the size is 100×80×3mm.

[0085] (3) Cut the vulcanized flexible silicone rubber into 80×10×3mm sizes, place it in a muffle furnace and heat it to 600℃, 1000℃ and 1600℃ respectively at a heating rate of 10℃ / min and hold it for 30min respectively. After cooling to room temperature (22-25℃), take it out to obtain ceramicized silicone rubber material. The test results are shown in Table 6.

[0086] Example 6:

[0087] (1) Stir 60 parts of filler body (alumina), 15 parts of flux (low melting point glass powder), 2.5 parts of binder (aluminum dihydrogen phosphate), 20 parts of heat compensation agent (silicon powder and aluminum powder in a 10:10 ratio) and 7.5 parts of flame retardant (aluminum hydroxide) at 1000 r / min for 30 min, then adjust the speed to 500 r / min, add 2.5 parts of shrinkage inhibitor (alumina fiber cotton) and stir for 30 min to obtain ceramic filler; mix 100 parts of methyl vinyl silicone rubber (platinum catalyst content is 0.5% of the total methyl vinyl silicone rubber) with 150 parts of ceramic filler by manual or mechanical stirring to obtain a mixture.

[0088] (2) The mixture is transferred into a mold, degassed under vacuum and extruded, and vulcanized at 40°C for 6 hours to obtain flexible silicone rubber with a specification of 100×80×3mm.

[0089] (3) Cut the vulcanized flexible silicone rubber into 80×10×3mm sizes, place it in a muffle furnace and heat it to 1600℃ at heating rates of 10℃ / min, 20℃ / min and 30℃ / min respectively, and hold it for 30min respectively. After cooling to room temperature (22-25℃), take it out to obtain ceramicized silicone rubber material. The test results are shown in Table 7.

[0090] Example 7:

[0091] Example 7 is basically the same as Example 1, except that in step (1), the mass ratio of methyl vinyl silicone rubber to ceramic filler is 100:220.

[0092] Example 8:

[0093] Example 8 is basically the same as Example 1, except that in step (1), the amount of adhesive additive (aluminum dihydrogen phosphate) added is 6 parts.

[0094] Example 9:

[0095] Example 9 is basically the same as Example 1, except that in step (1), the amount of shrinkage inhibitor (alumina fiber cotton) added is 6 parts.

[0096] Example 10:

[0097] Example 10 is basically the same as Example 1, except that in step (1), the amount of thermal compensator (silicon powder) added is 30 parts.

[0098] Comparative Example 1:

[0099] Comparative Example 1 is basically the same as Example 1, except that: in step (1), the ceramic filler does not contain a binder (aluminum dihydrogen phosphate).

[0100] Comparative Example 2:

[0101] Comparative Example 2 is basically the same as Example 1, except that in step (1), the ceramic filler does not contain shrinkage inhibitor (alumina fiber cotton).

[0102] Comparative Example 3:

[0103] Comparative Example 3 is basically the same as Example 1, except that in step (1), the ceramic filler does not contain thermal compensating agent (silicon powder and aluminum powder).

[0104] Comparative Example 4:

[0105] Comparative Example 4 is basically the same as Example 1, except that in step (1), the filler body is replaced with sericite.

[0106] The ceramicized silicone rubber materials prepared in Examples 1 to 10 and Comparative Examples 1 to 4 (hereinafter referred to as samples) were subjected to performance tests and macroscopic morphological changes were observed. The test results are as follows: Figures 1 to 7 As shown in Tables 1 to 8.

[0107] Specifically, the mass loss rate (m a () refers to the percentage change in the weight m1 of the sample after high-temperature heat treatment relative to the weight m0 before heat treatment;

[0108] Linear shrinkage rate (l) a The length l1 of the sample after high-temperature heat treatment is the proportion of the change in size l0 before heat treatment. The sample dimensions are 80mm × 10mm × 3mm. The calculation formulas for the two are as follows:

[0109]

[0110] The bending strength of the sintered samples was determined according to the national standard GB / T 9341-2008. The bending strength of the samples after heat treatment at different temperatures was tested using an INSTRON-5969 universal testing machine with a loading rate of 2 mm / min.

[0111] The formula for calculating bending strength is:

[0112]

[0113] In the formula,

[0114] σ f — Bending strength, in MPa;

[0115] F – The applied pressure, measured in nanometers (N).

[0116] L—span of the sample, in mm;

[0117] b — width of the sample, in mm;

[0118] h — the thickness of the sample, in mm.

[0119] Table 1

[0120]

[0121] Table 2

[0122]

[0123]

[0124] Table 3

[0125]

[0126] Table 4

[0127]

[0128] Table 5

[0129]

[0130] Table 6

[0131]

[0132]

[0133] Table 7

[0134]

[0135] Table 8

[0136]

[0137] Note: The heating rate is 10℃ / min, and the holding time at 1600℃ is 30min.

[0138] From Tables 1 to 8 and Figures 1 to 8 As can be seen from the above, compared with the comparative example, the ceramicized silicone rubber prepared in the embodiments of the present invention can be ceramicized at temperatures below 600°C, and the ceramicized silicone rubber material still has good mechanical strength (i.e., flexural strength). At the same time, due to the reasonable selection and control of the amount of ceramicized filler, the ceramicized silicone rubber material prepared in the embodiments of the present invention has both low thermal shrinkage, high temperature resistance and high mechanical strength.

[0139] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A ceramicized silicone rubber material, characterized in that, It is composed of methyl vinyl silicone rubber and ceramic filler; the methyl vinyl silicone rubber contains a platinum catalyst, the content of which is 0.5-1.0% of the total amount of methyl vinyl silicone rubber; the viscosity of the methyl vinyl silicone rubber is 5000~20000 mPa·s, and the mass ratio of methyl vinyl silicone rubber to ceramic filler is 100:(100-200). The ceramic filler comprises a filler body, a flux, a binder, a heat compensator, a shrinkage inhibitor, and a flame retardant. The filler body is alumina; the flux is low-melting-point glass powder with a melting point of 350-580℃; the binder is at least one of aluminum dihydrogen phosphate, aluminum polyphosphate, or aluminum metaphosphate; the heat compensator is composed of silica powder and aluminum powder, with a mass ratio of silica powder to aluminum powder of (5-20):(5-20); the shrinkage inhibitor is alumina fiber cotton, with a fiber diameter of 3-4 micrometers and an alumina content greater than 95%; and the flame retardant is aluminum hydroxide. The ceramic filler has the following composition: 40-80 parts of filler body, 10-20 parts of co-solvent, 0.5-5 parts of binder, 10-40 parts of heat compensator, 0.5-5 parts of shrinkage inhibitor and 5-13 parts of flame retardant. The filler body, co-solvent, binder, heat compensator and flame retardant are all in powder form with a particle size of 5-100 micrometers.

2. The material according to claim 1, characterized in that, The composition of the ceramic filler is as follows: 55-65 parts of filler body, 15-18 parts of co-solvent, 2-3 parts of binder, 15-25 parts of heat compensator, 2-3 parts of shrinkage inhibitor and 12-13 parts of flame retardant.

3. The method for preparing the ceramicized silicone rubber material according to any one of claims 1 to 2, characterized in that, The preparation method includes the following steps: (1) Mix methyl vinyl silicone rubber with ceramic filler to obtain a mixture; (2) The mixture is placed in a mold for vulcanization to obtain flexible silicone rubber; (3) The flexible silicone rubber is placed in a muffle furnace for heating and ceramicizing to obtain the ceramicized silicone rubber.

4. The preparation method according to claim 3, characterized in that, In step (2), the temperature of the sulfidation reaction is 22-24℃, and the time is 7-10 days; or The vulcanization reaction is carried out at a temperature of 40-42℃ for 5-6 hours.

5. The preparation method according to claim 3, characterized in that, In step (3), the heating temperature for ceramicization is 500-1600℃, the heating rate is 10-30℃ / min, and the time is 30-90min.

Citation Information

Patent Citations

  • Coatable ceramic silicone rubber and preparation method therefor

    CN105623273A

  • Preparation method of ceramic silicon rubber composite material used for fire-resistant insulated cable

    CN105647190A

  • Expansible ceramic silicone rubber composite material and preparation method thereof

    CN107760038A

  • Waterproof anti-aging ceramicized silicon rubber material and preparation method and application thereof

    CN108948743A